Landscape construction of urban wetland park based on ecological aesthetics research. Issue 6 (June 2020) - Shaoying, Zhang; Mei, Wu
Abstract: According to the relevant theoretical research of landscape ecological aesthetics, landscape construction in urban wetlands will be analyzed. The ecological aesthetic framework constructed on this basis can be used to understand the development status and research significance. By combing the relevant concepts, theories about the major ecological aesthetics will be part of the concern. These will be used to construct a theoretical framework for landscape construction. Proceed from the awakening of ecological aesthetic consciousness to explore the beauty of natural ecological balance and the construction of human ecological beauty. On this basis, it puts forward a harmonious view of ecological aesthetics and looking for various connections between people and landscape elements in ecological aesthetics. These will be used to emphasize the complexities of natural aesthetics and the construction of urban wetland landscape ecological aesthetics.